Planning activity of the public administration in the area of family protection and care - Krygier, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The study is aimed at presenting a group of instruments used in Polish administrative law to protect a family. The main focus is placed on showing a variety of plans, programmes, strategies and other similar forms of activity of public administration, which are issued by the state administration and self-government administration. Special attention is paid to a legal nature of plans and tasks connected with planning.